Analysis of the Influence of CRM (Customer Relationship Marketing) Through Communication, Commitment, Trust and Conflict Management on Customer Retention Case Study: Warung Banbet - Putra, Diki Ariansyah; Harmain, Hendra; Imsar, Imsar (Universitas Trunojoyo Madura, 2024)
This research aims to determine the effect of Customer Relationship Marketing consisting of: Communication, Commitment, Trust, and Conflict Management on Customer Retention at Warung Banbet. This type of research uses a descriptive quantitative type. The sample in this study used a purposive sampling technique which resulted in a research sample of 97 respondents. The analysis tool used for this study was SPPS For Windows 30. Based on the tests carried out with multiple linear regression analysis, the results of the study showed that. (1) communication, commitment, trust, and conflict management have a positive and significant effect partially and simultaneously on customer retention at Warung Banbet. (2) communication, commitment, trust, and conflict management get results from the F test of 60.7% (3) from the results of the study, the variable that has the strongest effect on customer retention is the Communication variable (x1) (4) implications of the study Customer Relationship Marketing consisting of: Communication, Commitment, Trust and Conflict Management have a simultaneous effect on customer retention at Warung Banbet..